Kampung KB Sebuah Model Pemberdayaan Masyarakat Berbasis Keluarga - Suharta, Rudy (Jurnal Riset Daerah, 2020)
As an innovation of Family Planning grand program, the establishment of Family Planning Village act as a breakthrough and a miniature of synergy of various actions. Family Planning Village is one of community empowerment model with family resilience based. Hopefully, this Family Planning Village could be a Family Planning Program exemplary which are better directed, integrated, well-planned, and sustainable. Family Planning Village which are located in Bantul first established in 2016 namely Jasem Family Planning Village and Cempoko Family Planning Village. In 2019 from 75 villages, 47 of those has initiated Family Planning Village. Author wants to know how far the role and cross-sector integration in achieving an excellence Family Planning Village. Mapping problems and alternative solutions are the ones that author finds enticing to deeper study and analyze, as well as providing alternative solution in developing Family Planning Village in Bantul Regency. Research method used in this study is descriptive qualitative method, which is a research focusing more on understanding a certain problem rather than seeing a problem to generalize. The finding of this study shows that commitment support and active role of all government agencies whether district, sub-district, and village government, as well as many other parties are very much defining the success and management of Family Planning Village. Public figures participation, religious leaders, and village government’s support are the most important in this case, starting from priority setup, target, and activity program that are done by community independently and sustainably.